Intersecciones entre los Modelos Territoriales y los Modelos de Desarrollo, en el ámbito del Medio Ambiente - Sotelo Navalpotro, José Antonio (Observatorio Medioambiental, 2007)
Throughout the present paper it is clearly stated the unsustainable character of many of the present tendencies of development that transcend the national scope, put in danger the quality of life, and many mean an important limit to the very own development considering the hypothesis that the cost of the inaction is higher than the one that brings about the implementation of changes. Likewise, it is brought to the for that the reduction and suppression of unsustainable systems of production and consumption, which are to a greater extent responsible for the threats to the survival of the current model, seem to us essential, from a territorial perspective. Thus, it is seen as indispensable the progressive use of real costs that add the consumption costs of the natural resources; the establishment of new requisites both in goods and in services that guarantee the efficiency in production, in terms of savings in energy, waste and natural resources; and the information and training in new ways of consumption. Summarizing, the existing intersections between the Territorial Models and the Development Models have been studied from an environmental perspective.